THE INFLUENCE OF MASTERING SOFT SKILL AND DIGITAL LITERACY ON THE WORK READINESS OF CLASS XII STUDENTS AT SMKN 30 JAKARTA - Bilqiis, Allysya Lailla; Febriantina, Susan; Widyastuti, Umi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research aims to determine and analyse the influence of mastery of soft skill and digital literacy on the work readiness of class XII students at SMKN 30 Jakarta. This type of research uses quantitative descriptive research. The population chosen by the researchers wa 173 class XII students majoring in culinary, hospitality and fashion design, class of 2023. Furthermore, the sample used was 119 students, where in determining this sample using the slovin formula with the purposive sampling method. The data in this study were analysed using multiple linear regression analysis and processed using the IBM SPSS Statistics 25 application. The result of this study used the t or partial test, soft skills have a significant influence on work readiness with a significant value of 4,259 > 1,980 and digital literacy has an influence which is significant for work readiness, the significant for work readiness, the significant value is 4,259 7,855 > 1,980 for class XII students at SMKN 30 Jakarta